Recycling of Ti6Al4V machining swarf into additive manufacturing feedstock powder to realise sustainable recycling goals. (10th May 2022) - Dhiman, Sahil; Joshi, Ravinder Singh; Singh, Sachin; Gill, Simranpreet Singh; Singh, Harpreet; Kumar, Rakesh; Kumar, Vinod
Abstract: This paper addresses the imperative need to develop sustainable recycle technologies for high value machining swarf generated during the processing of Ti6Al4V alloy. A novel recycling process based on multi-stage ball milling is proposed. The process converts Ti6Al4V swarf into a powder feedstock suitable for additive manufacturing (AM). The powders produced from the cleaned swarf using an in-house designed and fabricated tumbler ball mill were characterised in terms of their morphology, particle size, flowability and spreadability. It was found that the dominant effect of milling with Ø 25 mm balls was particle size reduction (up to ∼ 40%) and the primary effect with smaller balls of Ø 6.25 mm was modification of particle morphology from irregular to rounded shape; thus, necessitating adoption of a multi-stage milling approach to achieve required size and morphology. Ti6Al4V powder having particle size in the range of 40–200 μm and near-spherical morphology was obtained after multi-stage ball milling up to 18 h. The powder characteristics were comparable or superior to the powder produced by generally used gas atomization (GA) process. The suitability of the powders for AM was established through direct metal laser sintering (DMLS). The proper melting of the optimally prepared powder occurs at 1000 mm/s scanning speed and 310 W of laser power. The developed multi-stage ball milling process was assessed vis-à-vis gas atomization using life cycle assessment (LCA). LCA revealed that the proposed ball milling method consumed lower energy (∼59%), had lower eco-cost (∼82%), and lesser global warming potential (GWP) (∼68%). Graphical abstract: Image 1 Highlights: Proposed process converts Ti6Al4V swarf into powder feedstock. Potential to produce powders with regulated characteristics. Particle size and morphology change depends on diameter of milling balls. Stress intensity and stress number increases with a decrease in ball size. Process consumes low energy has lesser eco-cost and global warming potential.